ANALISIS PREDIKSI FINANCIAL DISTRESS DENGAN MODEL ALTMAN Z - SCORE PADA PT. SMARTFREN TELECOM TBK PERIODE 2017-2023 - Ihwan Satria Lesmana (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
Smartfren Telecom Tbk. is one of the telecommunications companies in Indonesia. The company has experienced losses in the last seven periods, from 2017 to 2023. It is feared that this condition will result in a high risk of a company experiencing financial distress or even bankruptcy. This research aims to find out, describe and explain the results of applying the analysis of the financial distress prediction model, namely the Altman Z”-Score model which is used to assess and predict potential bankruptcy with research objects at PT. Smartfren Telecom Tbk for the 2017-2023 period. The method used in this research is a descriptive method using a qualitative approach, and the operational variables used are independent variables, namely a bankruptcy prediction model with the dependent variable being financial ratios. The data used is secondary data in the form of PT's annual financial report. Smartfren Telecom Tbk for the 2017-2023 period. Results of financial distress analysis using the Altman Z”-Score model at PT. Smartfren Telecom Tbk for the 2017-2023 period, shows that the company is in a state of distress because the average Z"-Score value is -2.9 or Z < 1.1. This research shows that analysis of bankruptcy or financial distress using the Altman Z"-Score model at PT. Smartfren Telecom Tbk for the 2017-2023 period concluded that the company was in a state of distress.